Senegal : Staff Report for the 2008 Article IV Consultation, First Review Under the Policy Support Instrument, and Request for Waiver of Assessment Criterion and Modification of Assessment Criteria; Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report, 2008)
Senegal's staff report for the 2008 Article IV Consultation highlights the rapidly rising energy and food prices, and the high inflation in 2007 that put pressure on the fiscal and external accounts. Senegal's macroeconomic policies were being pursued under an economic program supported by the IMF's Policy Support Instrument (PSI), which was approved in November 2007. Executive Directors observed scope for improving the targeting of the existing measures while minimizing economic distortions so that they remained consistent with macroeconomic stability and debt sustainability.